Insights into interactions of Cr(III) and organic matters during adsorption onto titanate nanotubes: Differential absorbance and DFT study - Ruoqi Ma; Ting Wang; Taobo Huang; Sun, Weiling; Shuang Qiao; Liu, Wen (Journal of Molecular Liquids, 2020)
Organic Matter (OM) with different molecular weight and functional groups can impact the adsorptive removal of metal ions, and the influence trend can be facilitated, inhibited or unchanged. However, the association capabilities of different ligands were superficially expounded. Based on the sorption behavior of Cr(III) onto titanate nanotubes (TNTs) with coexisting citric acid (CA), humic acid (HA) and fulvic acid (FA), this study highlighted differential absorbance and DFT simulations to quantitatively detect the mutual effect. As results, adsorption capacities of Cr(III) obviously enhanced from ca. 60 mg/g to 85 mg/g with CA or FA; while HA can slightly promote Cr(III) adsorption. UV spectra scanning proved that FA and HA led to the remarkable red shift of peak A1 (232 nm), A2 (262 nm), A3 (295 nm), A4 (431 nm) of Cr(III), and the area ratio of A2/A3 followed the order Cr-HA > Cr-FA > Cr-CA ≈ Cr. DFT calculations further confirmed that the simultaneous formation of ligand-metal-adsorbents complex and electrostatic effect promoted Cr(III) adsorption, with binding energies of −202.9   −420.8 kJ/mol and − 3958 kJ/mol, respectively. Meanwhile, the bridge connection of OM mainly appeared in the outer sphere of TNTs, as the larger molecular scale prevented their insertion into the inner spacing of TNTs, especially for HA and FA. Therefore, the adsorption mechanism was the combined actions of electrostatic attraction, bridge connection of OM and steric effect. This study can give insights into OM effects on metal adsorption, and quantificationally describe the junction state of ternary complex.
Keywords: Adsorption; Binding energy; Cr(III); Organic matter; Titanate nanotubes